Energy saving technology for feed concentrates of vitamin b12 using methods of discrete-pulse input energy (DPIE) - Draganov, B.; Obodovych, O.; Lymar, A. (Енергетика і автоматика, 2015)
Studied the possibility of using discrete pulse input of energy (DPIE) in the technology of feed concentrate vitamin B12. It was established that the use of this method will reduce the duration of the fermentation process from 72 to 48 hours and increase the concentration of B12 in vita mute methane brazhtsi from 800 to 880 mg/l compared with the classical method of fermentation.